Hematological Variations Among SARS-COV-2 Patients Attending Zhyan Hospital at Ranya District, Iraq - Ahmed, Aesha Hassan; Mohammed, Sulaf Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2022)
Millions of people throughout the world have been impacted by the global pandemic virus SARS-COV-2. There is a paucity of information on the impact of SARS-COV-2 on hematological parameters in Kurdistan. To assess the effect of several physiological and pathological factors on the severity of the disease, this study looks at the hematological parameters among SARS-COV-2 patients hospitalized at Zhyan Hospital in Ranya, Kurdistan Region, Iraq. 200 cases were recruited for this study between 28th of September and 31st of December 2021. 50 negative people made up the control group, while 150 SARS-COV-2 patients mild, severe, and critical cases formed the study's three main study groups. The patients in the three groups were compared in terms of their hematological characteristics. The study revealed that compared to controls, SARS-COV-2 patients had significantly increased levels of white blood cells, granulocytes, platelet-large cell ratio, monocyte, red distribution width, platelet distribution width, platelet and decreased lymphocytes. WBC count, granulocyte, platelet-large cell ratio, monocyte, red distribution width, and platelet distribution width were all considerably higher in the critical group of SARS-COV-2 patients than in the severe and mild groups. Additionally, critical patients had considerably higher levels of lymphocytopenia and thrombocytopenia than severe and mild patient groups. Additionally, the critical group contained the highest proportion of SARS-COV-2 patients with concomitant conditions such as hypertension, diabetes and cardiovascular disease. The illness severity of SARS-COV-2 infection is nearly correlated with age, comorbidity, and levels of WBC, Lymphocyte, Granulocyte, Platelets, and P-LCR. Additionally, our results based on basic laboratory data may be useful in early illness severity prediction, and to improve the SARS-COV-2 patient survival rate.
Keywords: Severity COVID-19; SARS-COV-2; Hematological parameters; Clinical characteristic; Complete blood count